Motor development and sensory processing skills in infants with congenital muscular torticollis: a cross-sectional study - Zorlular, Rabia; Burak, Sinem Erturan; Beyoglu, Rana; Elbasan, Bulent (Springer, 2025)
Congenital muscular torticollis (CMT) is characterized by asymmetric head posture due to unilateral shortening or fibrosis of the sternocleidomastoid (SCM) muscle. This study aimed to evaluate motor development and sensory processing skills in infants with CMT and compare them with typically developing peers. In this cross-sectional study, term infants aged 4-6 months with muscular-type CMT and age-matched controls were assessed at Gazi University between February and May 2025. Motor development was evaluated using the Peabody Developmental Motor Scales-Second Edition (PDMS-2), and sensory processing was assessed via the Test of Sensory Functions in Infants (TSFI). In infants with CMT, the thickness of the SCM muscle was measured using computer-assisted ultrasonography. A total of 22 infants with CMT (10 females) and 21 typically developing peers (9 females) participated in the study. Demographic characteristics were similar between groups. Compared to controls, infants with CMT had significantly lower scores in TSFI tactile deep pressure (p = 0.01), ocular-motor control (p < 0.001), and total score (p = 0.002), as well as in PDMS-2 gross (p = 0.03), fine (p = 0.04), and total motor scores (p = 0.02). Effect sizes were moderate to large (Cohen's d = 0.79 for total motor, d = 1.12 for total TSFI).Conclusion: Infants with congenital muscular torticollis show delays in sensory processing and motor development. Early developmental screening and intervention may help identify and address these difficulties.Trial registration: The study was registered on ClinicalTrials.gov on March 10, 2025, under the number NCT06879314. What is Known:center dot The unilateral shortening or tightness of the sternocleidomastoid muscles can limit neck and head movements.center dot Limited range of motion impairs vestibular and proprioceptive input, negatively affecting balance and body awareness.What is New:center dot Infants with congenital muscular torticollis may exhibit delays in both gross and fine motor development compared to their typically developing peers.center dot Infants with congenital muscular torticollis may also demonstrate impairments in sensory processing skills, including tactile and ocular-motor domains.
Keywords: Congenital muscular torticollis; Sensory processing skills; Motor development; Ultrasound